Sobreduración y situación académica de los ingresantes a la Escuela Profesional de Medicina Veterinaria de la Universidad Nacional Mayor de San Marcos en el periodo 2004-2013 - Perales Camacho, Rosa (2022)
The aim of this study was to evaluate the excessive duration of the study program and the academic situation of the entrants of the Professional School of Veterinary Medicine (EPMV) of the Universidad Nacional Mayor de San Marcos. The study followed up on entrants between 2004 and 2013, whether or not they had completed their studies. The formal graduation time was established at seven years (formal excess duration index = 1.0) and the time for timely graduation at eight years (timely excess time index = 1.0). By 2022, 78% of entrants had completed their studies, 21% had dropped out, and 42% had a professional degree. The average time from entry to obtaining the professional degree was 10.1 years. The formal excess duration rate was 1.45, so graduates needed 45% more time (about 3 years) to achieve their degree, while the timely excess duration rate was only 1.27. In conclusion, there is a low percentage of graduates graduated from the EPMV.